PENGARUH RASIO MANAJEMEN AKTIVA, LIKUIDITAS DAN LAVERAGE TERHADAP PROFITABILITAS EMITEN SYARIAH SEKTOR BASIC MATERIAL DI BURSA EFEK INDONESIA - Fitri, Nabila Jannatun; Safaruddin, Safaruddin; Mizan, Mizan (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract : This study aims to test the effect of the Influence of Asset Management Ratio, Liquidity and Leverage on the Profitability of Sharia Issuers in the Basic Material Sector Listed on the Indonesia Stock Exchange. This study uses a quantitative method with multiple linear data analysis techniques. The sample used in this study was 29 companies with a research period of 2020-2022. The TATO variable has a significant effect on ROA. However, the CR variable in absolute terms has a significant negative effect on and the DAR variable in absolute terms has a significant negative effect on ROA. The TATO, CR, and DAR variables together have a simultaneous effect on ROA, this is indicated by the significance value so that it can be concluded that Ha4 is accepted that there is a simultaneous influence of TATO, CR and DAR on ROA with the results of the determination coefficient test (R Square), of 0.478 which means that the TATO, CR, DAR variables are able to explain the ROA variable 47.8%. Keywords: Total Assets Turn Over (TATO), Current Ratio (CR) Debt To Asset Ratio (DAR) Return On Assets (ROA)